2019
DOI: 10.3390/ijms20246315
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium and Lead Decrease Cell–Cell Aggregation and Increase Migration and Invasion in Renca Mouse Renal Cell Carcinoma Cells

Abstract: Metastatic renal cell carcinoma (RCC) remains an important clinical issue; the 5-year survival rate of patients with metastasis is approximately 12%, while it is 93% in those with localized disease. There is evidence that blood cadmium and lead levels are elevated in RCC. The current studies were designed to assess the impact of cadmium and lead on the progression of RCC. The disruption of homotypic cell–cell adhesion is an essential step in epithelial-to-mesenchymal transition and tumor metastasis. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Lead toxicity has also been shown to promote renal tumor formation in a large number of studies, and higher lead levels in the blood are linked with RCC [ 48 , 49 ]. Cadmium and lead induce phenotypic changes related to RCC cell aggregation, migration, and invasion [ 50 ]. GSEA analysis in our study showed that MT1X is notably involved in both hypoxia and metal ion homeostasis regulation, which are essential factors in the occurrence and progression of ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Lead toxicity has also been shown to promote renal tumor formation in a large number of studies, and higher lead levels in the blood are linked with RCC [ 48 , 49 ]. Cadmium and lead induce phenotypic changes related to RCC cell aggregation, migration, and invasion [ 50 ]. GSEA analysis in our study showed that MT1X is notably involved in both hypoxia and metal ion homeostasis regulation, which are essential factors in the occurrence and progression of ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…The affinity difference between SLC39A14A and SLC39A14B for Cd 2+ is a result of alternative splicing [10]. Cd 2+ can promote cell migration and invasiveness and is reported to promote the process of RCC [34], indicating that SLC39A14B is a promoter of RCC. In short, SRSF1 promoted the alternative splicing of SLC39A14 into SLC39A14B, which aggravated RCC.…”
Section: Discussionmentioning
confidence: 99%